DEDIFFERENTIATED LIPOSARCOMA PAYUDARA (LAPORAN KASUS) - Lintong, Poppy M.; Tambajong, Eddy H. (UNIVERSITAS SAM RATULANGI, 2011)
Abstrak: Liposarkoma primer pada payudara termasuk salah satu tumor payudara yang sa-ngat jarang, insidennya kurang dari 1% dari semua tumor ganas payudara. Umumnya liposarkoma pada payudara jarang atau tidak menyebar ke kelenjar getah bening aksila. Gambaran histologik liposarkoma pada payudara sama dengan liposarkoma di ekstrimitas atau tubuh. Suatu liposarkoma yang sejati pada payudara ditegakkan bilamana gambaran cystosarcoma phyllodes tidak ditemukan dalam potongan-potongan jaringan tumor. Satu kasus dilaporkan pada seorang wanita usia 49 tahun dengan tumor payudara besar. Gambaran Dedifferentiated Liposarcoma secara makroskopik menunjukkan massa multinoduler besar, warnanya bervariasi dari kuning, kuning kecoklatan bercampur coklat keabu-abuan. Mikroskopik terdiri dari 2 komponen yaitu lipogenik, menunjukkan gambaran liposarkoma diferensiasi baik; dan nonlipogenik (dedifferentiated). Daerah dedifferentiated menunjukkan gambaran fibrosarkoma, malignant fibrous histiocytoma, dan liposarkoma miksoid. Daerah yang menyerupai malignant fibrous histiocytoma menunjukkan gambaran sitologik pleo-morfisme, arsitektur storiform, dan sel-sel datia. Fokus-fokus liposarkoma miksoid telah dibuat pulasan dengan Alcian blue hasilnya positip. Kata kunci: dedifferentiated liposarcoma, payudara. Abstract: Primary liposarcoma of the breast belongs to very rarely found breast tumors, hav-ing an incidence of less than 1% of all malignant breast tumors. In general, this liposarcoma rarely or does not spread to axillar lymph nodes. Histopathologically, liposarcoma of the breast is similar to liposarcoma in extremities and other parts of the body. A true liposarcoma of the breast is diagnosed if there is no cystosarcoma phyllodes in the tumor tissues. We re-ported a 49-year-old female with a huge breast tumor (21x18x15cm), associated with four lymph nodes in the ipsilateral axilla. Histopathological examination of the tumor tissues showed a dedifferentiated liposarcoma, and of the four lymph nodes, as well as reactive hyperplasia with no metastase. Macroscopically, this dedifferentiated liposarcoma, appeared as large multinodular masses ranging in color from yellow to yellow-tan admixed with firm tan-gray areas. Microscopically, it consisted of two components: lipogenic, a well differen-tiated liposarcoma; and nonlipogenic, dedifferentiated one. These dedifferentiated areas showed a fibrosarcoma, malignant fibrous histiocytoma, and mixoid liposarcoma. Areas of malignant fibrous histiocytoma looked cytologic pleomorphisme, storiform architecture, and multinucleate cells. Foci of mixoid liposarcoma were stained with Alcian blue, and showed positive results. Key words: dedifferentiated liposarcoma, breast.